2008
DOI: 10.1364/oe.16.019674
|View full text |Cite
|
Sign up to set email alerts
|

Long-range surface polaritons in ultra-thin films of silicon

Abstract: Abstract:We present an experimental and theoretical study of the optical excitation of long-range surface polaritons supported by thin layers of amorphous silicon (a-Si). The large imaginary part of the dielectric constant of a-Si at visible and ultraviolet (UV) frequencies allows the excitation of surface polariton modes similar to long-range surface plasmon polaritons on metals. Propagation of these modes along considerable distances is possible because the electric field is largely excluded from the absorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…This work was extended by Yang and co-workers to non-metallic materials with very large absorption at infrared frequencies [26]. Giannini et al [27] and Arnold et al [28] demonstrated the excitation of long-range guided modes at optical frequencies in strongly absorbing films. These modes, described by Eq.…”
Section: Guided Modes Along Absorbing Thin Layersmentioning
confidence: 90%
See 1 more Smart Citation
“…This work was extended by Yang and co-workers to non-metallic materials with very large absorption at infrared frequencies [26]. Giannini et al [27] and Arnold et al [28] demonstrated the excitation of long-range guided modes at optical frequencies in strongly absorbing films. These modes, described by Eq.…”
Section: Guided Modes Along Absorbing Thin Layersmentioning
confidence: 90%
“…(3) defines also the dispersion of short-range modes in thin layers of absorbing dielectrics. However, these short-range modes are leaky waves that do not propagate along the slab [26,27]. In order to illustrate the characteristic lengths of long-range guided modes along water films, we consider the system formed by a thin layer of water homogeneously surrounded by a lossless and non-dispersive dielectric with permittivity ε 1 = ε 3 = 2.36.…”
Section: Guided Modes Along Absorbing Thin Layersmentioning
confidence: 99%
“…Figure 2(b) displays the reflectance measured for s-polarized incident light. The LRGM resonance is not present for this polarization, given that this mode is only supported for p-polarization [6,7,10]. The resonance at angles lower than 65 • is due to a Fabry-Pérot resonance into the PMMA layer.…”
Section: Experimental Demonstration Of Lrgms Emissionmentioning
confidence: 91%
“…This coupling reduces the energy density inside the thin film and provides the long-range propagation characteristics of these modes [7][8][9]. Even though the characteristics of LRGMs in terms of confinement and propagation are not as good as those of LRSPPs, LRGMs in strongly absorbing thin layers can propagate 10's to 100's of vacuum wavelengths along the layer, while still being confined within a wavelength to the surface [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, plasmonic excitation can be also obtained in the far infrared zone using doped semiconductors 21,22 or in the ultraviolet zone using aluminium or silicon, in particular, the latter offers the possibility to excite ultraviolet long-range surface polaritons in extremely thin films 23 . However, metals present high non-radiative losses that lead to unwanted heating limiting some of their applications in photonics.…”
Section: Introductionmentioning
confidence: 99%